2019
DOI: 10.1186/s41182-018-0127-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal characterisation and risk factor analysis of malaria outbreak in Cabo Verde in 2017

Abstract: BackgroundCabo Verde is a country that has been in the pre-elimination stage of malaria since the year 2000. The country is still reporting cases, particularly in the capital of Praia, where more than 50% of the national population live. This study aims to examine the spatial and temporal epidemiological profile of malaria across the country during the 2017 outbreak and to analyse the risk factors, which may have influenced the trend in malaria cases.MethodsLongitudinal data collected from all malaria cases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 41 publications
4
26
0
Order By: Relevance
“…To ensure elimination can be sustained and to support the prevention to reintroduction phase, the malaria case data collected as part of routine surveillance from the decade before interruption can be valuable for characterizing the malaria epidemiology and identify risk factors for improved surveillance activities. Therefore, this research extends previous research about malaria cases in the country [13,14] and characterizes both individual and spatial risk factors for endemic and introduced malaria infections.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…To ensure elimination can be sustained and to support the prevention to reintroduction phase, the malaria case data collected as part of routine surveillance from the decade before interruption can be valuable for characterizing the malaria epidemiology and identify risk factors for improved surveillance activities. Therefore, this research extends previous research about malaria cases in the country [13,14] and characterizes both individual and spatial risk factors for endemic and introduced malaria infections.…”
Section: Introductionsupporting
confidence: 70%
“…The sustained low levels of transmission, strong public health system and active malaria programs in the country indicate that the archipelago is a good candidate to achieve elimination in the African sub-region. [12,17] Although the epidemic that occurred in Praia in 2017 resulted in 423 locally acquired cases, there were no deaths and showed that the country is able to effectively contain transmission [14]. Given the likelihood of continued malaria importation from continental African countries the risk pro les of imported identi ed here will be helpful in prioritizing resources.…”
Section: Discussionmentioning
confidence: 98%
“…From 2010 to 2016, Cabo Verde has recorded a few cases of malaria [6], is considered by the WHO as potentially able to eliminate malaria by 2020. However, an increase in 2016 and the outbreak recorded in 2017 with 446 cases [7], demonstrated weaknesses and challenges in the disease control.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria has been classified as the fifth of the six major diseases in the country, which is likely related to few malaria cases recorded in the country, between 2010 and 2016 compared to other countries in the sub-region [6,7,[22][23][24][25]. Therefore, the Cape Verdean population, excepted in the islands of Santiago and Boavista, are less in contact with malaria in their daily lives, thus losing their knowledge about malaria.…”
Section: Knowledge About Malariamentioning
confidence: 99%
See 1 more Smart Citation